Calculation Results for Enhancing Ability of I-131 Radioisotope Production Using Tellurium Dioxide Target on the Dalat Nuclear Research Reactor - Nguyen Kien, Cuong; Huynh Ton , Nghiem; Le Vinh, Vinh; Luong Ba, Vien; Pham Quang, Huy; Tran Quoc, Duong; Bui Van, Cuong (Nuclear Science and Technology, 2021)
The paper presents the calculation results in re-design of neutron trap of the Dalat Nuclear Research Reactor (DNRR) for I-131 radioisotope production using TeO2 target. The new design permits for loading more TeO2 capsules from 9 to 12, 15 and 18 in the neutron trap. The enhancement of radioisotope production was implemented by re-arrangement of the neutron trap without changing the dimension or geometry of irradiation capsules. By using neutronics computer code as MCNP6, the obtained calculation results of I-131 activity in 6 investigated cases showed that the new design by the re-arrangement of the neutron trap can be used effectively for radioisotope production with thermal neutron flux in average range from 5.3×1012 to 1×1013 n/cm2.s and the total activity of I-131 isotope was increased from about 19.2% to 38.8% comparing with the original design using 9 capsules. The negative reactivity insertion was from 0.60 βeff to 0.96 βeff when loading capsules that also met the safety requirements of operational conditions of the DNRR.